1974
DOI: 10.1055/s-0028-1097985
|View full text |Cite
|
Sign up to set email alerts
|

ROOT ALKALOIDS OFRAUWOLFIA OREOGITON

Abstract: The indole alkaloids ajmalicine, ajmaline, rescinnamine, reserpiline, reserpine, a-yohimbine, another yohimbine isomer, renoxydine and serpentine were de-' tected in the root bark of R. oreogiton MGF. Reserpiline, reserpine and ajmaline were the principal alkaloids. Confusion concerning the identities of Rauwolfia volkensii STAPF and R. oreogiton M G F. resulted in the assumption that the species were synonymous because silviculturists regarded the species as doubtfully distinct (WILLAN, 1960). &lore recent co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1976
1976
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Subsequent work [10] extended the list and added ajmalicine, rescinnamine, renoxidine and a-yohimbine; the principal alkaloids found were reserpine, ajmaline and reserpiline. The present work further extends the list to include isoreserpiline, aricine, carapanaubine and yohimbine but serpentine was not detected.…”
Section: Alkaloidmentioning
confidence: 99%
“…Subsequent work [10] extended the list and added ajmalicine, rescinnamine, renoxidine and a-yohimbine; the principal alkaloids found were reserpine, ajmaline and reserpiline. The present work further extends the list to include isoreserpiline, aricine, carapanaubine and yohimbine but serpentine was not detected.…”
Section: Alkaloidmentioning
confidence: 99%
“…MONACHINO (BISSET, 1961) suggested that there was a typical northern R. verticillata occurring in China and Burma and a southern R. perakensis type occurring in Malaysia. WAN (1959) stated that the types could be readily distinguished by qualitative and quantitative microscopy. It was concluded that R. verticillnta represents a species complex, R. canzbodiana being a member of the group.…”
Section: Ajmaline Heteroyohimbine Basesmentioning
confidence: 99%
“…The extracts of the leaves and roots have been used as an antihypertensive preparation named verticilum. Previous investigations of this plant have shown that species of Rauvolfia are rich sources of bioactive indole alkaloids, such as reserpine [4][5][6][7][8][9][10][11]. Since our current interest includes all natural products, we investigated not only the indole alkaloids but also other types of chemical constituents with important biological activity in Rauvolfia.…”
mentioning
confidence: 99%